Identifikasi Bahaya dan Penilaian Risiko Kebakaran di Perusahaan Tekstil X Sukoharjo - Jordan Syah Gustav; Sumardiyono Sumardiyono; Lusi Ismayanti; Maria Paskita Widjanarti; Tutug Bolet Atmojo; Farhana Syahrotun Nisa S; Bekti Utomo; Seviana Rinawati; Warda Yussy Rha (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
This research aims to identify potential hazards and assess the level of fire risk in a textile company located in Sukoharjo Regency using the Hazard Identification, Risk Assessment, and Risk Control (HIRARC) method. The research background is based on the high fire hazard potential in the textile industry due to the use of flammable chemicals, high operating temperatures, and the accumulation of combustible fibers and textile dust. A descriptive research approach was applied through field observations, interviews with workers and the OHS team, and technical document analysis. The results showed that the highest risk levels were found in the dyeing process, electrical panel room, and machine maintenance activities (welding/repair), with risk scores reaching 20 (high category). The main contributing factors included non-standard electrical installations, poor ventilation, and unsafe work behavior. Risk control strategies are recommended through technical, administrative, and behavioral approaches, including smoke detection systems, routine evacuation training, and the reinforcement of safety culture. The implementation of these measures is expected to improve the effectiveness of occupational health and safety management systems and reduce the potential for fire incidents in the textile industry.